Enhancement of the therapeutic efficacy of the MAP regimen using thiamine pyrophosphate‐decorated albumin nanoclusters in osteosarcoma treatment - So‐Yeol Yoo; Yong‐Hyeon Mun; Nae‐Won Kang; Jang Mo Koo; Dong Hwan Lee; Ji Hoon Yoo; Sang Min Lee; Seokjin Koh; Jong Chan Park; Taejung Kim; Eun Kyung Shin; Han Sol Lee; et al. (Wiley, 2023)
Abstract Recent studies on osteosarcoma regimens have mainly focused on modifying the combination of antineoplastic agents rather than enhancing the therapeutic efficacy of each component. Here, an albumin nanocluster (NC)‐assisted methotrexate (MTX), doxorubicin (DOX), and cisplatin (MAP) regimen with improved antitumor efficacy is presented. Human serum albumin (HSA) is decorated with thiamine pyrophosphate (TPP) to increase the affinity to the bone tumor microenvironment (TME). MTX or DOX (hydrophobic MAP components) is adsorbed to HSA‐TPP via hydrophobic interactions. MTX‐ or DOX‐adsorbed HSA‐TPP NCs exhibit 20.8‐ and 1.64‐fold higher binding affinity to hydroxyapatite, respectively, than corresponding HSA NCs, suggesting improved targeting ability to the bone TME via TPP decoration. A modified MAP regimen consisting of MTX‐ or DOX‐adsorbed HSA‐TPP NCs and free cisplatin displays a higher synergistic anticancer effect in HOS/MNNG human osteosarcoma cells than conventional MAP. TPP‐decorated NCs show 1.53‐fold higher tumor accumulation than unmodified NCs in an orthotopic osteosarcoma mouse model, indicating increased bone tumor distribution. As a result, the modified regimen more significantly suppresses tumor growth in vivo than solution‐based conventional MAP, suggesting that HSA‐TPP NC‐assisted MAP may be a promising strategy for osteosarcoma treatment.